Вес и размеры оленей пятнистых (Cervus nippon Теmm.) с острова Аскольд - Присяжнюк, В.Е. (Вестник зоологии, 1973)
Body dimensions, absolute and relative weight of organs are presented for 12 Cervus nippon T e m m. shot in Askold island in summer and at the beginning of winter in 1967. The deers from the island are close to the park ones by the size but considerably inferior to wild deers from the Sudzukhian reservation.